2006
DOI: 10.1074/jbc.m508758200
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in the Plasminogen-binding Group A Streptococcal M Protein Family

Abstract: Group A streptococci (GAS) display receptors for the human zymogen plasminogen on the cell surface, one of which is the plasminogen-binding group A streptococcal M protein (PAM). Characterization of PAM genes from 12 GAS isolates showed significant variation within the plasminogen-binding repeat motifs (a1/a2) of this protein. To determine the impact of sequence variation on protein function, recombinant proteins representing five naturally occurring variants of PAM, together with a recombinant M1 protein, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…However, in the Northern Territory of Australia, where streptococcal skin infection is endemic and high rates of invasive infection such as bacteremia have been reported (10), PAM-positive GAS are associated with a variety of disease states (11). The plasminogen binding domain of PAM has been shown to be highly variable; however, this diversity does not abrogate plasminogen binding by naturally occurring PAM variants (12). This finding may, in part, be due to the conservation of key amino acid residues within the plasminogen binding domain (11,12).…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…However, in the Northern Territory of Australia, where streptococcal skin infection is endemic and high rates of invasive infection such as bacteremia have been reported (10), PAM-positive GAS are associated with a variety of disease states (11). The plasminogen binding domain of PAM has been shown to be highly variable; however, this diversity does not abrogate plasminogen binding by naturally occurring PAM variants (12). This finding may, in part, be due to the conservation of key amino acid residues within the plasminogen binding domain (11,12).…”
mentioning
confidence: 82%
“…Site-directed Mutagenesis-The PAM gene from streptococcal strain NS13 (PAM NS13 GenBank TM AY351851), which is identical to the prototype PAM sequence in the a1 and a2 repeat domain, had previously been cloned into the expression vector pGEX2T (12). To assess the role of specific-binding site residues in the interaction of PAM with plasminogen, site-specific mutations were introduced into the PAM NS13 -binding site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine Plasminogen Purification-Plasminogen was isolated from porcine plasma as described previously (27,28). MALDI Q-TOF tandem MS, performed according to Henrich et al (26), confirmed the purified protein as plasminogen.…”
Section: Methodsmentioning
confidence: 99%